PENERAPAN KURIKULUM MERDEKA PADA MATA PELAJARAN IPS DI SMP NEGERI 4 SIGI - Syahdan, Muh.; Hakim, Moh. Arfan; Hamzah, Erni Irmayanti (Citra Media Publishing, 2024)
This study aims to analyze the implementation of the Merdeka Curriculum in IPS subjects at SMP Negeri 4 Sigi “With the main problem, namely how the implementation of the Merdeka Curriculum in IPS subjects at SMP Negeri 4 Sigi. And describe the obstacles and solutions that teachers do in implementing the Merdeka Curriculum in IPS Subjects at SMP Negeri 4 Sigi. This study uses a qualitative descriptive method, which describes the aspects that are the target of writing research, data collection techniques through observation, interviews, and documentation, data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that the form of implementation of the Merdeka Curriculum in IPS subjects at SMP Negeri 4 Sigi is by giving freedom to educators, including principals, teachers, and students to determine topics or themes that they are interested in and want to learn. They are also free to determine learning methods that suit their needs. The implementation of learning is divided into 2 main activities, namely intracurricular learning oriented towards learning outcomes (CP) and co-curricular in the form of projects for achieving the Pancasila Student Profile and the Rahmatan lil Alamin Student Profile. However, the observations made by researchers show that it is true that teachers still have difficulties in implementing learning based on this Merdeka Belajar Curriculum. This is in accordance with the observations made by researchers that teachers are still difficult to in still the 6 characters of the Pancasila Student Profile to students with various characteristics.